A case of sclerosing odontogenic carcinoma: a rare entity. Issue 4 (April 2023) - Cutmore, Natasha; Chengot, Preetha
Abstract: Sclerosing odontogenic carcinoma (SOC) is a very rare entity, first recognized in the WHO 4 th edition (2017). It is a highly infiltrative intraosseous jaw tumour with small nests, strands and cords of cells showing only mild cytological atypia, surrounded by a dense fibrocollagenous stroma. The lesion frequently infiltrates adjacent tissues and bony structures and demonstrates perineural and intraneural invasion. The malignant islands of cells may be compressed by the stroma, making them difficult to identify. On immunohistochemistry, they are positive for cytokeratins (including CK5/6, CK14, CK19) and p63. Several other (more common) lesions present in a similar way and show similar histological features, and need to be excluded before establishing a diagnosis of SOC. Here, we present a case in a 37 year old male who presented with a several month history of a lump over the right mandible.